Biblia na tle pism sakralnych ludów ościennych - Stanek, Teresa (Wydział Teologiczny UAM, 2010)
Comparative studies of the Bible and the sacred texts of adjacent nations have a rich tradition, but research generally focuses on comparing passages of the biblical text with adequate sacral texts of adjacent nations. However, this approach involves two problems: 1* difference of religious status - the Bible is a living reality, whereas the sacral texts of other ancient nations of the Near East are only relics; 2* form of the writings - the Bible is a uniform work, modified by the conscious acts of communities of faith while the writings of adjacent nations survive to our times only in fragments. The article takes off from a different comparatistic conception. My primary concern is not so much to bring out the similarities or discrepancies between Bible passages and adequate sacral texts of adjacent nations but rather to show the whole canon of the holy scriptures of Israel against the backdrop of the sacred writings of the Region. The comparison is built on two assumptions: 1 * origin and usage; 2* addressee of the text. Therefore, it does not refer to the question of literary genres but first and foremost to the dependencies between the text and the community.
The Bible against the Backdrop of the Sacred Texts of Adjacent Nations
Keywords: Bible; ancient Near East; sacral texts; canon